REFORMULATING THE APPLICABLE STRATEGIES IN IMPROVING FINANCIAL LITERACY AND INCLUSION INDEX TOWARD ISLAMIC CAPITAL MARKET - Syafwendi Syafril (Universitas Islam Negeri Ar-Raniry, 2021)
Indonesia’s financial inclusion and literacy index level in the Islamic capital market sector is quietly low at around 0.02% and 0.01%. Though Indonesia is known as a country with the largest Muslim population in the world with more than 85%. Furthermore, the fact of Indonesia is the 4th highest growth country in the capital market industry in Asia-Pacific throughout 2017. The potential for growth and development of the Islamic capital market in Indonesia is very high, but this fact is not followed by the growth rate of financial literacy and inclusion index especially in the capital market sector. The aim of this paper is to identify the new applicable strategic approach to improve Islamic financial literacy and inclusion in term of Islamic capital market sector. This research uses qualitative methods with a literature review from the article journal, government report, news report, and others in reviewing, identifying, and knowing the strategies that will be implemented. The results show there are six specific strategies used in improving Islamic capital market literacy and inclusion indexes namely, rebranding investment negative stereotype, building a sustainable promotion and campaign through offline and online platform, creating an online integrated marketplace for Islamic capital market products, improving corporate Sukuk and introducing a new SRI Sukuk product, forming agents & groups of Islamic capital market lovers, and monitoring & evaluating the applied strategy.